Identification and characterization of Colletotrichum fioriniae and C. fructicola that cause anthracnose in pecan - Chang, Jun; Zhai, Fengyan; Zhang, Yabo; Wang, Di; Shu, Jinping; Yao, Xiaohua (Frontiers in Plant Science, 2022)
Abstract: Pecan (Carya illinoinensis Wang. K. Koch) is a deciduous tree of the Juglandaceae family with important economic value worldwide. Anthracnose of the pecan leaves and shuck is a devastating disease faced by pecan-growing areas in China. However, the causal species occurring on pecan remain largely unidentified. Therefore, we collected samples of diseased pecan from the provinces of China. Leaves and fruits affected by anthracnose were sampled and subjected to fungus isolation, resulting in a total of 11 Colletotrichum isolates. The morphological characters of all strains were observed and compared. Multi-locus phylogenetic analyses (Internally transcribed spacer (ITS), Actin (ACT), Calmodulin (CAL), Chitin synthase (CHS¬1), Glyceraldehyde 3-phosphate dehydrogenase (GAPDH), and β-tubulin (TUB2)) were performed on selected representative strains. Two Colletotrichum species were identified to be C. fioriniae and C. fructicola. The former infected the shuck, while the latter infected both the shuck and leaves. Pathogenicity tests revealed that both species caused black spots on pecan leaves and fruit. The virulence of the different isolates varied substantially, with C. fioriniae PCJD179 being the most virulent. The susceptibility levels of pecan tree varieties, ‘Mahan’ and ‘Kanza’, were determined. No significant differences were observed in the lesion sizes produced by the various isolates in ‘Kanza’, while there were significant differences in ‘Mahan’. This study is the first to determine that C. fructicola and C. fioriniae can cause anthracnose in pecan in China. It improves the understanding of the species that cause anthracnose in pecan and provides useful information for the effective control of this disease in China.